Martí and Emerson like antecedents of the ecosophic thinking - González Sivilla , Roeris; Méndez Santos , Isidro Eduardo; Varela Aristigueta , Matilde Teresa (Transformación, 2024)
The article describes one of the findings of the research project "Epistemological foundations of environmental education". An analytical and comparative reading of José Martí texts addressing the issue of nature together with excerpts of the work of Ralph Waldo Emerson was completed to find out common criteria between the two thinkers and then contextualize these ideas in the context of the foundations of Ecosophy. It was possible to identify Emerson’s thinking about natures, the worldwide view of José Martí, and the vision of both thinkers on the relation natural-society as epistemological referents of ecosophic knowledge.
Keywords: Ecosophy; ecosophic thinking; environmentalism; environmental education; Marti's thought